Reapropiaciones: mujeres, arte y espacio. Andrea Luquin Calvo y Carmen Guiralt Gomar (editoras), “Comares Arte”, nº 15, Granada, Editorial Comares, 156 pp. ISBN: 978-84-1369-842-7 - Rodríguez-Fernández, M. Gracia (Arte, Individuo y Sociedad, 2025)
Disponible en Open Access en: https://accesoabiertocomares.com/index.php/coa/catalog/book/69